The Concordance between Myocardial Perfusion Imaging and Coronary Angiography in Detecting Coronary Artery Disease: A Retrospective Study in a Tertiary Cardiac Center at King Abdullah Medical City - Fatma Aboul-Enein; Majed O. Aljuaid; Hail T. Alharthi; Abdulkarim M. Almudhhi; Mohammad A. Alzahrani (Cardiology Research and Practice)
Background. Coronary artery disease (CAD) is considered as the leading cause of the cardiovascular fatalities worldwide. CAD is diagnosed by many modalities of imaging such as myocardial perfusion imaging (MPI) and coronary angiography (CAG). Methods. A retrospective cross-sectional study was conducted that included all patients referred to the KAMC (King Abdullah Medical City) nuclear cardiology lab from its opening until the end of May 2014 (a period of 17 months). A total of 228 patient reports with a history of conducting either CAG or MPI or both were used in this study and statistically analyzed. Results. An analysis of the MPI results revealed that 78.5% of the samples were abnormal. On the other hand, 26.75% of the samples revealed that they were subjected to CAG and MPI. There was a significant and fair agreement between MPI and CAG by using all the agreement coefficients (kappa = 0.237, phi = 0.310, and P value = 0.043). The sensitivity, specificity, and accuracy of MPI with reference to CAG were 97.8%, 20%, and 78.69%, respectively. In addition, positive predictive and negative predictive values were 78.95% and 75%, respectively. Conclusion. In a tertiary referral center, there was a significant agreement between MPI and CAG and a high accuracy of MPI. MPI was a noninvasive diagnostic test that could be used as a gatekeeper for CAG.